55 A MOBILITY PROFILE OF STROKE PATIENTS ADMITTED TO A LEVEL 4 ACUTE HOSPITAL OVER A 6-MONTH PERIOD. (25th October 2022) - Murphy, D; Crowley, A; Fitzpatrick, M
Abstract: Background: In order to best direct physiotherapy stroke resources and further service development it is important to characterise the mobility of stroke patients presenting to an acute hospital. Methods: A previous audit completed in 2018 in the same organisation established that by using the Berg Balance Scale (BBS) and the Mobility Scale for Acute Stroke (MSAS) as admission outcome measures, a baseline profile could be established while limiting the floor and ceiling effects. A retrospective audit was completed of all patients referred to the stroke physiotherapy service admitted with acute stroke in a 6 month period. An excel spreadsheet was used to record patients' admission BBS and MSAS. This was recorded along with the mainstay of physiotherapy treatment and discharge destination. Results: 145 stroke patients were assessed by stroke physiotherapy between Oct 2021 and April 2022. Of those patients 30% scored full marks on the MSAS which indicates that they were independently mobile with or without an aid post stroke. 26% of patients scored 3 or less on the BBS which would imply they were unable to sit without help. Conclusion: This audit provides valuable information on the mobility profile of stroke patients presenting to an acute Level 4 hospital. On admission, patients seem to fall into 3 distinct categories based on their physical function post stroke. One group remained independently mobile post stroke, one group were heavily dependent being unable to sit without assistance and the final cohort requiring some level of supervision or assistance for mobility and balance. This information could be used to facilitate therapy and resource planning.